Application of GIS Models in Determining the Suitable Site for a Solid Waste to Energy Plant in an Urban Area - Ali Basha; Ahmed Salem; Wael Mostafa; Magda H. Farhan (Salehan Institute of Higher Education, 2024)
This paper deals with the establishment of a solid waste-to-energy plant that significantly reduces the volume of solid waste and produces electricity at the same time. Thirteen criteria have been identified to locate the station based on environmental, economic, and social factors to avoid its negative impacts. These criteria were addressed by combining a Multi Criterion Decision Making (MCDM) method based on the GIS software. This study aims to establish a MCDM system based on the classical AHP and validated by the fuzzy AHP method. The findings revealed that using the classical AHP and fuzzy AHP methods, there was no significant difference in decision-making between the two methods. The importance of the criteria under study has been identified based on the judgments of experts; a questionnaire was designed and conducted electronically, which was collected with the help of a weighted overlay GIS model. This technique combines multiple reclassified data in ArcGIS 10.8 software to overlay criteria layers with different weights to create a composite map of suitability categories across the study area. The outcomes revealed that 96.76% of the study area is unsuitable for establishing the station, 1.36% is moderately suitable, and 0.04% is only very suitable for station site selection. Doi: 10.28991/CEJ-2024-010-01-011 Full Text: PDF